Diet dependent life history, feeding preference and thermal requirements of the predatory mite Neoseiulus baraki (Acari: Phytoseiidae) - Domingos, C.A.; Melo, J.W.D.S.; Gondim, M.G.C.; Moraes, G.J. de; Hanna, R.; Lawson-Balagbo, L.M.; Schausberger, P. (Springer, 2010)
Neoseiulus baraki Athias-Henriot (Acari: Phytoseiidae) has been reported from the Americas, Africa and Asia, often in association with Aceria guerreronis Keifer (Acari: Eriophyidae), one of the most important pests of coconut (Cocos nucifera L.) in different parts of the world. That phytoseiid has been considered one of the most common predators associated with A. guerreronis in Brazil. The objective of this study was to evaluate the feeding preference and the effect of food items commonly present on coconut fruits and several temperature regimes on the life history of a Brazilian population of N. baraki. Completion of immature development was possible when N. baraki was fed A. guerreronis, Steneotarsonemus concavuscutum Lofego and Gondim Jr., and Tyrophagus putrescentiae (Schrank). Fecundity was highest on T. putrescentiae (39.4 eggs), followed by A. guerreronis (24.8 eggs). In choice tests, irrespective of the food on which N. baraki was reared, a larger number of adults of this predator chose leaf discs containing A. guerreronis than discs containing other food items, demonstrating a preference of the former for the latter as food. Egg to adult thermal developmental time was calculated as 84.2 degree-days, above a threshold of 15.8°C. This lower developmental threshold is higher than previously published for phytoseiid species from higher latitudes. Neoseiulusbaraki was shown to have higher biotic potential at 30°C (rm 0.29). The results suggest N. baraki to be a promising biological control agent of A. guerreronis, well adapted to survive and develop in areas with relatively high temperatures, where that pest prevails.